2010
DOI: 10.1038/ejcn.2010.9
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of coffee on endothelial function in healthy subjects

Abstract: Background/Objectives: Coffee is the most widely consumed beverage in the world, but its effect on the cardiovascular system has not been fully understood. Coffee contains caffeine and antioxidants, which may influence endothelial function, both of which have not yet been investigated. The objective of this study was to investigate the acute effects of coffee on endothelial function measured by brachial artery flow-mediated dilation (FMD). Subjects/Methods: A total of 20 (10 males and 10 females) healthy non-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
3
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 52 publications
3
62
3
5
Order By: Relevance
“…Figure 1 summarizes our previously reported results regarding the effects of caffeinated (Buscemi et al, 2010) and decaffeinated (Buscemi et al, 2009) coffee on the brachial artery FMD with respect to the characteristics of the two tested espresso coffees.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 summarizes our previously reported results regarding the effects of caffeinated (Buscemi et al, 2010) and decaffeinated (Buscemi et al, 2009) coffee on the brachial artery FMD with respect to the characteristics of the two tested espresso coffees.…”
Section: Resultsmentioning
confidence: 99%
“…This study indicates that both caffeinated and decaffeinated espresso coffee, which acutely influence FMD (Buscemi et al, 2009(Buscemi et al, , 2010, have significant anti-oxidant properties. This activity was approximately 15% higher in caffeinated coffee, probably because of a slight loss of antioxidant substances with decaffeinization procedures (Parras et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that acute administration of coffee has a harmful effect on endothelial function in healthy subjects [24,25], while other studies have shown that coffee improves endothelial function [26,27]. In addition, the association between coffee drinking and risk of cardiovascular disease remains inconclusive [15,[17][18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been conflicting results regarding the association between coffee drinking and risk of cardiovascular disease [19][20][21][22][23]. The effect of coffee on endothelial function is also controversial [24][25][26][27]. One possible reason for the different results of studies is that the contents of chlorogenic acids, which are the most abundant antioxidants in coffee, may vary depending on several factors [16].…”
Section: Introductionmentioning
confidence: 99%